Abdominal adiposity and low physical activity are independently and inversely associated with bone mineral density. Issue 6 (November 2017) - Krishnan, Chandramouli; Choksi, Palak; Peterson, Mark D.
Highlights: The link between regional adiposity and skeletal health is not well understood. We tested the association between adiposity and BMD in a large sample of US adults. Abdominal adiposity and BMI have significant, yet opposing influences on BMD. Abdominal adiposity is negatively associated with BMD in both men and women. Our findings contradict the notion that excess body mass is protective for bone health. Summary: Background and Methods: Obesity is a highly heterogeneous condition, and the link between adiposity distribution profiles and skeletal health is not well understood. This study examined the association between adiposity and bone mineral density (BMD) in a large cohort (5268 individuals) of US adults aged 20–85 years. Results: Body mass index (BMI) and moderate-to-vigorous physical activity were positively associated with BMD. Conversely, abdominal adiposity was negatively associated with BMD, even after adjusting for age, race, BMI, and objectively-measured physical activity. Conclusions: These findings highlight the negative influence of abdominal adiposity on BMD and contradict the notion that excess fat mass is protective for bone health.